An Insight into Storage Lipid Synthesis by Yarrowia lipolytica Yeast Relating to Lipid and Sugar Substrates Metabolism - Agata Fabiszewska; Paulina Misiukiewicz-Stępień; Magdalena Paplińska-Goryca; Bartłomiej Zieniuk; Ewa Białecka-Florjańczyk (Biomolecules, 2019)
Single cell oil (SCO) is the lipid accumulated in the cells of oleaginous microorganisms. Cellular lipids can be synthesized in two different pathways: de novo by metabolizing hydrophilic substrates and ex novo by fermenting hydrophobic substrates. The aim of the study was to evaluate the effect of carbon source (glucose and olive oil) in the culture medium on the course of microbial oil accumulation in Y. lipolytica cells. The level of selected gene expression by real time quantitative PCR method was investigated. The significant increase in expression of the POX2 gene encoding acyl-CoA oxidase II, which preferentially oxidizes long-chain acyl-CoAs formed from substrate fatty acids incorporated inside the microbial cell, was observed in medium with olive oil in relation to glucose containing medium. Noteworthily, the presence of lipid carbon substrate did not inhibit the level of ACL gene transcription coding for ATP-citrate lyase, the key enzyme of the lipid de novo accumulation process. The present study indicated that de novo lipid biosynthesis could occur despite the presence of fatty acids in the medium, and the synthesis of storage lipids in the presence of lipid carbon substrates could be carried out with the use of both pathways (de novo and ex novo).